PENERAPAN NUMBER HEADS TOGETHER (NHT) BERMEDIA JARUM PINTAR UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS DAN MOTIVASI BELAJAR - Wulandari, Novita; Aeni, Ani Nur; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2019)
Classroom Action Research in this study is an improvement of the problems found by teachers in learning, namely the lack of analytical skills and student motivation. Improvement aims to improve planning, implementation, learning motivation, and ability to analyze students. The subject was a fift- grade student at Pasirbenteng II Elementary School. As a result, the implementation of the Number Heads Together (NHT) model with Jarum Pintar can improve teacher performance in the first cycle planning stage 81.8%, cycle 2 93.9%, cycle 3 100%, phase 1 implementation cycle 81.3%, cycle 2 92 %, cycle 3 100%, student learning motivation criteria very good cycle 1 48%, cycle 2 64%, cycle 3 92%, ability to analyze cycle 1 32%, cycle 2 52%, cycle 3 89%. Then it is evident that the application of NHT models with Jarum Pintar can improve the ability of students to analyze and learn motivation on material forms of human interaction with their environment.